Usulan Perubahan Terbatas Undang-Undang Dasar Republik Indonesia Tahun 1945 Mengenai Perencanaan Pembangunan Nasional Model Garis-Garis Besar Haluan Negara - Putri, Prima Widya; Walintukan, Maria Fransiska (Faculty of Law, Universitas Slamet Riyadi, 2023)
The emergence of the State Policy Guidelines (GBHN) discourse has been revived all this time because of the disappointment of many parties related to the development process whose outputs and outcomes are not in line with expectations and are not coherent. The development process is seen as being overemphasized on the limited perspective of the President or Regional Head elected, resulting in development disparities that are still far from expectations. Therefore, there is a thought to propose a limited amendment to the 1945 Constitution of the Republic of Indonesia concerning the GBHN model of national development planning. The things that will be explained are the Legal Products of the National Development Planning of the GBHN model, the Process of Forming the National Development Planning of the GBHN model, the Legal Implications of the National Development Planning of the GBHN model, Recommendations for the National Development Planning Content of the GBHN model. This type of research conducted is normative legal research, or often known as the normative juridical approach. In the fifth amendment to the 1945 Constitution the position of the MPR would still be a high state institution but the granting of authority to the MPR in determining the GBHN was a form of mechanical check and balance in the administration of state life.